Effectiveness of home-based exercise combined with nutritional care intervention in elderly patients with gastric cancer and sarcopenia: a retrospective study - Chun-Jing Yang; Chun-Jing Yang; Li Chen; Li Chen; Li Chen; Qing Zhou; Qing Zhou; Hui Hou; Hui Hou; Feng-Yi Xie; Feng-Yi Xie (Frontiers in Medicine)
BackgroundSarcopenia and malnutrition are prevalent among elderly patients with gastric cancer, significantly impairing recovery and quality of life (QoL). Effective interventions targeting both nutritional and physical deficiencies are critical. This study evaluated the effectiveness of a home-based exercise combined with nutritional care intervention in improving nutritional status, patient-generated subjective global assessment (PG-SGA) scores, and QoL among elderly patients with gastric cancer and sarcopenia.MethodsA retrospective evaluation was conducted on 126 elderly patients (aged ≥ 65 years) with gastric cancer and sarcopenia between January 2021 and December 2023. Patients were divided into two groups: the observation group (n = 61) received a home-based exercise combined with nutritional care intervention, while the control group (n = 65) received standard oncological nursing care. Nutritional status was assessed using biomarkers (albumin, prealbumin, transferrin) and PG-SGA scores, while QoL was measured using the Generic Quality of Life Inventory-74 (GQOLI-74). Data was analyzed using independent t-tests and Chi-square tests, with p < 0.05 considered statistically significant.ResultsBaseline characteristics were comparable between the groups (P > 0.05). Following the intervention, the observation group exhibited significantly greater improvements in nutritional biomarkers compared to the control group: albumin (41.80 ± 5.45 g/L vs. 32.25 ± 5.37 g/L, t = 9.905, P < 0.001), prealbumin (288.59 ± 25.95 mg/L vs. 219.20 ± 23.05 mg/L, t = 15.89, P < 0.001), and transferrin (2.28 ± 0.28 g/L vs. 1.77 ± 0.23 g/L, t = 11.20, P < 0.001). The observation group’s PG-SGA scores decreased significantly (1.28 ± 0.28 vs. 4.33 ± 0.56 in the control group, t = 38.28, P < 0.001). QoL scores in physical, psychological, social, and material life domains also showed substantial improvements in the observation group compared to the control group (P < 0.001 for all).ConclusionThe home-based exercise combined with nutritional care intervention significantly enhanced nutritional status, reduced PG-SGA scores, and improved QoL in elderly patients with gastric cancer and sarcopenia. This integrated approach demonstrates its value as an effective strategy for comprehensive cancer care, addressing both physical and nutritional deficits to optimize recovery outcomes.